Quality of board members’ training and bank financial performance: evidence from Portugal - Pereira, V. M. M. (2019)
This study examines the impact of the quality of board members’ training on the financial performance of Portuguese banks. The study employs a sample of 276 board members. Financial ratios such as return on average assets (ROAA) and return on average equity (ROAE) are used as measures for gauging banks’ financial performance. Three indexes are used as proxies for board members’ educational qualifications, specifically: Eduindex, for all academic qualifications obtained in areas such as business or economics; EduindexDP, for all qualifications obtained in prestigious domestic business schools; and EduindexFP, for all qualifications obtained in prestigious foreign business schools. The study findings have important policy implications, specifically a positive and significant impact on the bank’s financial performance from having board members holding degrees from prestigious foreign business schools. In particular, the findings suggest that the prudential supervision developed by Banco de Portugal in cooperation with the European Central Bank should include a more rigorous process in the selection of board members. The present study is one of the first attempts in the literature emphasizing all these aspects simultaneously, that is, the banking sector, quality of board members’ training, and Eduniversal Rankings, in the context in which all the banks of a specific country are analysed. © 2018 International Strategic Management Association.